Integration of Defense Policy and Public Policy From a National Security Perspective in Countering Hybrid Warfare Threats - Rubiyanto P Aji; Asep Adang Supriyadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
The threat of hybrid warfare is now a crucial issue in national security, so the state is required to unite military-based defense policy with public policy. An integrated approach based on national security analysis is key in shaping a resilient national defense system that is ready to face the evolving challenges of hybrid warfare. Literature studies are used to collect, analyze, and synthesize various related studies by identifying, collecting, and analyzing various sources such as journal articles and other relevant data to formulate a framework for the integration of defense policy and public policy in counteracting hybrid warfare threats through a national security perspective that utilizes technology and stakeholder collaboration. This research reveals that hybrid warfare is a complex form of threat that combines physical and non-physical tactics that require states to design adaptive and integrated defense policies and public policies. The national security perspective shows a collaborative approach across sectors, such as economic stability and the use of advanced technology for threat mitigation. Therefore, the integration of defense and public policies is key in building a responsive, flexible, and sustainable national strategy in the face of dynamic and multidimensional hybrid warfare challenges. This research confirms that in facing increasingly hybrid threats, the state needs to adopt an adaptive, integrated, and technology-based national security approach through the formulation of defense and public policies that include strengthening socio-economic resilience, cross-sector collaboration, and the use of artificial intelligence to maintain stability and strengthen national resilience against the dynamics of global threats.